Implementasi Kegiatan Sadar Baca dan Tulis (SABTU) dalam Meningkatkan Literasi Santri di Pondok Pesantren Mamba’ul Hikmah Ponorogo - Safitri, Laila Nur; Makruf, Imam (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The purpose of this study was to determine the implementation of the Sadar Baca dan Tulis (SABTU) activity carried out at the Mamba'ul Hikmah Kauman Islamic Boarding School in Kota Lama Ponorogo and its impact on students. This research uses a qualitative case study approach. Researchers went directly to the Mamba'ul Hikmah Islamic Boarding School by interviewing the caregivers, administrators and students of the Mamba'ul Hikmah Islamic Boarding School. Data collection techniques using interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman model. The results showed that SABTU activities aim to improve students' literacy skills, which not only include reading and writing but also logical and critical thinking. This activity is carried out by students reading selected books which are then summarized and presented the next day, on Sunday, in an activity called EPIS. SABTU activities show a positive impact on every santri who participates in them. It is proven that after literacy activities, many students enjoy reading and writing, and some of them even create their own written works. This research is expected to provide valuable insights into effective practices in improving literacy in Islamic educational institutions.